RELIABILITY OF CERTAIN TESTS FOR EVALUATION OF JUDO TECHNIQUES - Slavko Obadov; Janoš Kopas (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
The sample included 106 judokas. Assessment of the level of mastership of judo techniques was carried out by evaluation of fi ve competent studies. Each subject performed a technique three times and each performance was evaluated by the judges. In order to evaluate measurement of each technique, Cronbach's coeffi cient of reliability  was calculated. During the procedure the subjects's results were also transformed to factor scores i.e. the results of each performer at the main component of evaluation in the fi ve studies. These factor scores could be used in the subsequent procedure of multivariant statistical analysis.